Ocean acidification alters the benthic biofilm communities in intertidal soft sediments - Zhai, Chuan; Liang, Yantao; Yu, Hao; Ji, Yan; Chen, Xuechao; Wang, Min; McMinn, Andrew (Frontiers in Marine Science, 2023)
Microphytobenthos (MPB) and bacterial biofilms play crucial roles in primary and secondary production, nutrient cycling and invertebrate settlement in coastal ecosystems, yet little is known of the effects of ocean acidification (OA) on these communities in intertidal soft sediments. To fill in this gap, a 28-day CO2 enhancement experiment was conducted for the benthic biofilms in soft intertidal sediments (muds and sands) from Qingdao, China. This experiment included three CO2 treatments: 400 ppm CO2 (control), 700 ppm CO2 and 1000 ppm CO2 (IPCC predicted value in 2100), which were established in a three-level CO2 incubator that can adjust the CO2 concentration in the overlying air. The effects of OA on benthic biofilms were assessed in the following three aspects: MPB biomass, biofilm community structure and microbial biogeochemical cycling (e.g., C-cycle, N-cycle and S-cycle). This study found that the 700 ppm CO2 treatment did not significantly affect the benthic biofilms in intertidal soft sediments, but the 1000 ppm CO2 treatment significantly altered the biofilm community composition and potentially their role in microbial biogeochemical cycin sediments (especially in sandy sediments). For the bacterial community in biofilms, the 1000 ppm CO2 enhancement increased the relative abundance of Alteromonadales and Bacillales but decreased the relative abundance of Rhodobacterales and Flavobacteriales. For microbial biogeochemical cycling, the 1000 ppm CO2 treatment enhanced the potential of chemoheterotrophic activity, nitrate reduction and sulfur respiration in sediments, likely resulting in a more stressful environment (hypoxic and enriched H2S) for most benthic organisms. Even though incubations in this study were only 28 days long and thus couldn’t fully accommodate the range of longer-term adaptions, it still suggests that benthic biofilms in intertidal sandy sediments are likely to change significantly near the end of the century if anthropogenic CO2 emissions unmitigated, with profound implications on local ecosystems and biogeochemical cycling.